I_2-Cesàro summability of double sequences of sets - Dündar, Erdinç; Ulusu, Uğur; Gülle, Esra (My University, 2015)
In this paper, we de ned concept of Wijsman I2-Cesàro summability and investigate the relationship between the concepts of Wijsman strongly I2-Cesàro summability, Wijsman strongly I2-lacunary convergence, Wijsman p-strongly I2-Cesàro summability and Wijsman I2-statistical convergence of double sequences of sets.
Keywords: Cesàro Summability; Wijsman Convergence; I_2-Convergence; Double Sequence